2005
DOI: 10.1016/j.jom.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Learning, communication, and the bullwhip effect

Abstract: We investigate the effect of learning and communication on the bullwhip effect in supply chains. Using the beer distribution game in a controlled laboratory setting, we test four behavioral hypotheses -bounded rationality, experiential learning, systems learning, and organizational learning -by systematically manipulating training and communication protocols. We find that order variability decreases significantly in a setting in which participants start with hands-on experience, and are then allowed to formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 45 publications
3
124
0
3
Order By: Relevance
“…Downstream stage is the direction towards the end customer; and upstream stage is the direction towards the end supplier. Forrester was the first person who noticed this phenomenon (Wu & Katok, 2006). In some industries, this effect is also known as whiplash or whipsaw effect.…”
Section: Introductionmentioning
confidence: 99%
“…Downstream stage is the direction towards the end customer; and upstream stage is the direction towards the end supplier. Forrester was the first person who noticed this phenomenon (Wu & Katok, 2006). In some industries, this effect is also known as whiplash or whipsaw effect.…”
Section: Introductionmentioning
confidence: 99%
“…Later Zhang (2005); again modeling customer demand as first order AR (i.e., AR(1)) process and using MMSE forecasting model, showed that delayed demand information reduces BWE. Machuca et al (2004) and Wu et al (2005) studied on the effects of information sharing to BWE. Machuca et al focused on the usage of EDI in SCN systems.…”
Section: Supply Chain Management 52mentioning
confidence: 99%
“…Based on the idea that usage of EDI reduces the information delays, Machuca et al analyzed the SCN system both as a whole and for individual echelons and showed that a reduction in BWE and related cost (especially costs driven by inventory) can be achieved with the usage of EDI, thought it did not completely eliminate the BWE in SCN systems. Wu et al (2005) used the beer game and analyzed the phenomenon from information sharing together with organizational learning perspective. Thought the study looked at the problem only in managerial view, the outcomes displayed that when organizational training and learning combined and coordinated thought data sharing and communication reduction in order oscillation could be achieved.…”
Section: Supply Chain Management 52mentioning
confidence: 99%
“…Additionally, compensation and assessment of work systems influence human behavior which in turn affects the performance of HR (Wirawan 2009). Wu and Katok (2006) state that leadership and interpersonal communication significantly affects employee performance. Moreover, inovation, interpersonal communication and performance-measurement systems have significant and positive impact on employees performance (Fleming 2009).…”
Section: Introductionmentioning
confidence: 99%